Borealin/CDCA8 deficiency alters thyroid development and results in papillary tumor-like structures - Didier-Mathon, Hortense; Stoupa, Athanasia; Kariyawasam, Dulanjalee; Yde, Sonny; Cochant-Priollet, Beatrix; Groussin, Lionel; Sébag, Frédéric; Cagnard, Nicolas; Nitschke, Patrick; Luton, Dominique; Polak, Michel; Carré, Aurore (Frontiers in Endocrinology, 2023)
Background: BOREALIN/CDCA8 mutations are associated with congenital hypothyroidism and thyroid dysgenesis. Borealin is involved in mitosis as part of the Chromosomal Passenger Complex. Although BOREALIN mutations decrease thyrocyte adhesion and migration, little is known about the specific role for Borealin in thyroid.We characterized thyroid development and function in Borealin-deficient (Borealin +/-) mice, using histology, transcriptome analysis, and quantitative PCR.Results: Thyroid development was impaired, with a hyperplastic anlage on embryonic day E9.5 followed by thyroid hypoplasia from E11.5 onward. Adult Borealin +/-mice exhibited euthyroid goiter and defect of thyroid hormone synthesis. Borealin +/-aged mice had disorganized follicles and papillary-like structures in thyroids due to ERK pathway activation and strong increase of Braf-like genes described by TCGA network of papillary thyroid carcinoma. Moreover, Borealin +/-thyroids exhibited structural and transcriptomic similarities with papillary thyroid carcinoma tissue from a human patient harboring a BOREALIN mutation, suggesting a role in thyroid tumor susceptibility.Conclusions: These findings demonstrate Borealin involvement in critical steps of thyroid structural development and function throughout life. They support a role for Borealin in thyroid dysgenesis with congenital hypothyroidism. Close monitoring for thyroid cancer seems warranted in patients carrying BOREALIN mutations.